Pelatihan Pembuatan Media Pembelajaran Matematika di SD Negeri Jatimekar 02 - Sri Awan Asri; A Rahim; Ilmi Noor Rahmad (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
In general, elementary school age children (SD) are experiencing development at their thinking level, elementary school children's thinking stages are still not formal and are still concrete in nature. Therefore, the teacher must present material that is real so that elementary students can understand the concept completely. Based on the results of interviews with several mathematics teachers and principals, information was obtained that mathematics learning is carried out very rarely using media, especially in the form of props or other innovative media. Regarding the above problems, we are interested in conducting training through a community service program entitled "PKM Training on Making Mathematics Learning Media at SDN Jatimekar 02." This PKM is carried out in the form of three meetings training. The training participants were a number of teachers at SDN Jatimekar 02 Pagi. The presentation material in this service activity is: (1) The concept of learning media that is in accordance with the characteristics of Mathematics subjects along with examples of implementation in learning (2) Making learning implementation plans (RPP) with appropriate learning media (3) Simulation of implementing cooperative learning media in learning, and (4) assessment of learning using instructional media. Based on the results of the evaluation, 28 out of 32 participants understood the concept of learning media well, 25 participants were able to develop plans for implementing learning using media, and 30 participants were able to use media when learning in class.